Poéticas anfibias. Bilingüismo y autotraducción en cinco poetas contemporáneos de expresión italiana, catalana, castellana y gallega - Marisa Martínez Pérsico (Catalonia)
This paper analyzes some of the modalities acquired by endogenous or exogenous bilingualism through the methodology of the case study. I present some linguistic biographies of poets from the historical communities of Spain, as well as from Italy and Latin America interviewed for this research: Fabio Morábito (Italy-Mexico), Gigliola Zecchin (Italy-Argentina), Yolanda Castaño (Spain: Galicia), Josep Maria Rodríguez (Spain: Catalonia) and Vanna Andreini (Italy-Argentina). Also included are comments by the Catalans Joan Margarit and Mireia Vidal-Conte and the Argentines Sylvia Molloy and Adrián Bravi. The study is completed with some reflections on vertical and horizontal self-translation, the role of schooling in bilingual competence and the impact of linguistic contact on the poetic idiolect (code switching, loanwords, calques, allusions, or intertextual quotations) as well as the coining somatic metaphors to describe one’s own bilingualism.